2013
DOI: 10.1016/j.jcot.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictive parameters for angiography and embolization in the bleeding pelvic fracture

Abstract: a b s t r a c tAim: In the bleeding pelvic fracture, decision needs to be made on definitive control of bleeding whilst resuscitation. The decision for angiography in unstable patients is difficult and this study hopes to identify the parameters that may aid in this decision. patients who underwent angiographic evaluation were identified. 11 out of the 15 had angiography and embolization done, while the remaining 4 only had angiography done.Another group of 29 patients who had not undergone angiography were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…Lunsjo et al [ 11 ] observed an association of mortality with ISS but not with the pelvic fracture pattern. Anandakumar et al [ 12 ] observed a link between Tile fracture patterns and arterial contrast extravasation with need for AAE. Hussami et al [ 13 ] found a significant correlation between the Tile fracture type and arterial, but not venous bleeding in a series of trauma patients who underwent postmortem CT. Rommens and Hessmann [ 9 ] not only found a higher mortality rate, but also worse functional outcomes when comparing type C with type B fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Lunsjo et al [ 11 ] observed an association of mortality with ISS but not with the pelvic fracture pattern. Anandakumar et al [ 12 ] observed a link between Tile fracture patterns and arterial contrast extravasation with need for AAE. Hussami et al [ 13 ] found a significant correlation between the Tile fracture type and arterial, but not venous bleeding in a series of trauma patients who underwent postmortem CT. Rommens and Hessmann [ 9 ] not only found a higher mortality rate, but also worse functional outcomes when comparing type C with type B fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Anandakumar et al identified 11 patients over a 5-year period who underwent angio-embolisation and their selection criteria are more liberal than ours. 6 The retrospective nature of our series and the low patient numbers reflect limitations of our study.…”
Section: Discussionmentioning
confidence: 92%
“…17,18,19 Successful embolisation rates for arterial injuries have been reported to be 85-100%. 1 In our study the delay from admission to angio-embolisation was considerably longer with a mean of 14 hours (range 4-24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiographic embolization is proven to be a safe and effective treatment method in patients with pelvic trauma [12]. For the treatment of arterial injury in pelvic fracture, aggressive angiographic embolization has a high success rate [1,[4][5][6][12][13][14]. Nevertheless, although many studies have reported on the indications for pelvic angiography, precise guidelines have yet to be established.…”
Section: Introductionmentioning
confidence: 99%